A relação entre o letramento digital e a formação leitora de crianças com deficiência intelectual matriculadas no Atendimento Educacional Especializado no contexto de uso do software Luz do saber infantil - Lima Sobrinho, Amadeu Fernandes de (2022)
This research was based on the historical-cultural theory, which in its genesis, presupposes the social dimension of learning as a result of the experiences of individuals in the social, historical and cultural environments. The use of digital technologies has reconfigured the reality of many Brazilian schools, but their insertion in the daily lives of children - particularly those with intellectual disabilities - rarely explores their replacing the real promotion of development by a technological palliative assistance, exclusionary, decontextualized and antipedagogical. Given this reality, this research aimed to analyze the relationship between the digital reading and reading training of children with intellectual disabilities, the use of the software Luz do Saber Infantil by teachers of the specialized educational service of the public network of Fortaleza. The theoretical foundation was based on the theories of learning from the historical-cultural perspective (VYGOTSKY, 1994; LEONTIEV, 2004; LURIA, 2005). The study also comprised three dimensions: the cognitive development of students with intellectual disabilities (FIGUEIREDO, 2012, 2014, 2016; GOMES, 2012, 2013, 2016; POULIN, 1989, 2013, 2020); the appropriation of reading (SOLÉ, 1998; KLEIMAN, 2013) and the digital Letramento (ARAUJO, 2014; STREET, 1995, 2003; COSCARELLI E RIBEIRO, 2014). The research, of a qualitative nature, was based on a database of the LER Research Group, from the year 2018. This collection was built in an action research developed by the group, which we participated as a scholar of scientific initiation. In this research, the methodological procedure consisted of three main stages: a) database survey; b) identification of software activities, which focused on the appropriation of reading and digital reading of participants; c) organization and analysis of data. In this study, three intervention sessions (1st, 6th, 9th) were selected from a total of ten, and two children, from eight participants of the original research. These children were in the process of literacy. The discussion of the data was based on the content analysis of Bardin (2011), which were organized into two thematic units: hypertextual reading and reading training. It was found that the two children frequently used hypertextual reading, as in the activities proposed by the software, they recognized images, letters, words and located the information contained in the activities. It is concluded that, despite the weaknesses identified in the scope of reading and short-term memory of both children, the appropriation of hypertextual reading allowed them to develop strategies to deal with the resolution of activities in the software and to overcome in part, these weaknesses. It was also observed other benefits such as, for example, the handling of the computer, reading comprehension, writing mobility, resolution of activities, variety of graphical representations on the keyboard and motivation of students in the face of activities in the digital environment, visual stimulus and contributed to the construction of children’s autonomy.